Parliamentary representation in colonial Algeria during the period of the military regime (1830-1870) - Salek, Ahmed Amine (The Algerian Historical Journal, 2026)
Parliamentary representation in Algeria during the military regime of 1830-1870 was one of the most important issues that demonstrated the true intention of the French administration towards the Algerian people. At all levels, all councils, whether municipal, financial, and public, the administration favored the French minority to the detriment of the majority of the population, all this to preserve its interests inside Algeria. As a result, the Algerians were unable to express themselves or to push through any of their plans to reduce the power of the French until the outbreak of the liberation revolution and the achievement of independence.